Are Shem and Ham blood brothers? The relevance of the Old Testament to Africa - Burden, J. J. (1983)
This paper explains the preference of the Old Testament by African people. The compatibility of the Old Testament with Africans lies in a common outlook on life and human existence, which results from a common experience of reality. The paper questions the method of searching for correspondences in the past. It points to some analogous or parallel fields of experience. viz. the sacred and the profane, man and his community, man and nature and sin and disease. Thereafter it investigates means of expressing common experience in three areas, viz. myth. ritual and wisdom. In summary the paper mentions the following two reasons why a comparison of the Old Testament with African thought is valuable: a) It has pedagogical value for it discovers correspond-ences and differences; and b) it has theological value for it indicates directions for a search for an African Theology.
Keywords: Comparison; Old Testament; common experience; preference by Africans; shared viewpoint